GeoSensor Networks - Stefanidis, Anthony (CRC Press, 2009)
Advances in sensor technology and deployment strategies are revolutionizing the way that geospatial information is collected and analyzed. The advent of nanotechnology makes it feasible to deploy low cost, low power devices with on-board sensing and wireless communications capabilities. As a result of this new sensor deployment reality, the fields of GIS and remote sensing face multiple research challenges related to real-time geosensor data collection, management, analysis, and delivery.